ANALISIS YURIDIS ATAS PENERAPAN ASAS KESEIMBANGAN DALAM PERJANJIAN KREDIT PERBANKAN (Studi Pada Bank Mega KCP MT. Haryono) - REZA ABDUH (PREMISE LAW JURNAL, 2018)
DOSEN PEMBIMBING:1. Muhammad Yamin2. T. Keizerina Devi A3. Syafnil Gani Generally, the contents of the credit agreement that the standard form (raw) the content is not balanced, in the sense of more benefit the creditors as the party that makes it. As an example, for example a standard clause in a credit agreement which contains the following: "The terms of the credit interest rate can be reviewed and restated unilaterally by the creditor.